Pengaruh Motivasi dan Disiplin Terhadap Kinerja Karyawan - Putriana; Maharani, Audina (Asosiasi Dosen Akuntansi Indonesia, 2025)
Motivation and work discipline are important aspects in improving employee performance in the company. Optimal performance can be achieved if employees have high motivation and are able to carry out tasks with good discipline. This study aims to analyse the effect of work motivation (X1) and work discipline (X2) on employee performance (Y). The method used is quantitative descriptive with multiple linear regression analysis processed through SPSS version 25. The population in the study consists of 40 people using the saturated sampling technique. Partially, work motivation (X1) has a positive and significant effect on employee performance (Y), while work discipline (X2) does not have a significant effect on employee performance (Y). Simultaneously, work motivation (X1) and work discipline (X2) positively and significantly influence employee performance (Y). Work motivation and work discipline affect employee performance by 92.4% and the remaining 7.6% is influenced by other variables.